Comparison of DNA stability and its related genes of neurons derived from induced pluripotent stem cells and primary retinal neurons. (30th June 2022) - Yu, Na; Qiu, Jin; Li, Kaijing; Luo, Qian; Liu, Xuan; Yang, Ying; Jiang, Zihua; He, Shengyu; He, Anqi; Chen, Shuilian; Chen, Xi; Li, Yan; et al.
Abstract: Maintaining DNA stability in induced pluripotent stem cells (iPSCs) and iPSCs‐derived neurons is a challenge in their clinical application. In the present study, we compared DNA stability between primary retinal neurons and differentiated neurons. We found that the basal level of γ‐H2AX phosphorylation, a specific marker of DNA breaks, was notably higher ( 26‐folds) in human iPSCs compared to iPSCs‐derived neurons. However, iPSCs‐derived neurons are more sensitive to UV treatment compared to primary rat retinal neurons (postnatal Day 1). UV treatment induced a significantly decreasing in the cell viability of iPSCs‐derived neurons by 76.1%, whereas 20.8% in primary retinal neurons. After analyzing the expression levels of genes involved in DNA stability, such as Brca1, Ligase IV, Ku80, and Mre11, we found that Ku80 and its heterodimeric partner, Ku70 were positive in iPSCs‐derived neurons. However, both Ku80 and Ku70 are not expressed in primary retinal neurons and cerebellar neurons. Similarly, both Ku80 and Ku70 are also expressed in 3D retinal organoids from human embryonic stem cells (ESCs), except for a few Map2‐negative cells and the hyaloid vessels of mice E12.5 retinas. Hence, Ku80, and Ku70 are specifically expressed in stem cell‐derived neurons. Moreover, using the Ku80 inhibitor Compound L, our data showed that Ku80 promotes the DNA stability and cell viability of iPSCs‐derived neurons. Thus, our results demonstrated that iPSCs‐, ESCs‐derived neurons have specific characteristics of DNA stability. This study provides new insights into the neural differentiation of stem cells but might also warrant the future clinical application of stem cells in neurodegenerative diseases.